THE MEDIATING ROLE OF MEDICAL REPRESENTATIVES - V S, Sreethy Mohan; Rani, R. Shoba (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Medical Representatives are a group of highly educated, smart, well-groomed people with good personality and behavior. Their role is to influence healthcare professionals to prescribe their product brand to their customers. The role of medical representative is very challenging one as they are the backbone of pharmaceutical industry. They inform and present their brand features in front of the physician, try to influence them for prescribing their product. They also try to understand the needs of physicians and communicate the same with higher officials. Thus, their feedback is very much useful to the research and development of the company. Medical representatives work as an intermediate between the company and healthcare professionals they are so much updated regarding their competitor’s product, price and its features. They build good relationships with doctors, chemists, stockiest as well as administrators by providing information about their brand and persuade them to promote their company products by prescribing the same to the patients. They also organize conferences for physicians for informing them about their company’s new product launch, features etc. briefly they perform versatile tasks and duties as a mediator of their company.